An evaluation of the frequency of cyanotic & acyanotic CHDs in children of Faisalabad (European journal of volunteering and community-based projects, 2022)
The aim of the research paper is to analyze the Frequency of Cyanotic and Acyanotic CHDs in children up to 2 years of age. And the secondary aim is to see the gold standard modality for the diagnosis of CHDs. The Consecutive Sampling was used based on 120 questionnaires conducted from Faisalabad Institute of Cardiology. The data was collected with the permission of Relevant department and with the consent of Patient. Data of 120 patients was collected with 60% male to 40% female ratio. Out of 120 referred children (neonates: 29.9%, less than 1 year: 50.2%, greater than 1 year: 19.9%) 93% were diagnosed as having congenital heart defects. The relative frequencies of cyanotic and acyanotic congenital heart defects were 17%, 83%. Majority of patients with congenital heart disease detected have acyanotic congenital heart defects. TOF is the commonest cyanotic defect and VSD acyanotic defect. To prevent complications Early detection of heart failure is very important for proper management. The 2D-echo with Doppler test creates a gold standard for diagnosis.
Keywords: Congenital heart defects; echocardiography; frequency of CHD; cyanotic heart defects; acyanotic heart defects